2022
DOI: 10.3390/vaccines10020247
|View full text |Cite
|
Sign up to set email alerts
|

How do Vaccinators Experience the Pandemic? Lifestyle Behaviors in a Sample of Italian Public Health Workers during the COVID-19 Era

Abstract: Public health workers (PHWs) have experienced substantial workload changes because of their role in managing measures to limit the spread of COVID-19. The study’s aim was to assess lifestyle changes in Italian PHWs during the pandemic. PHWs attending an annual meeting completed an anonymous questionnaire assessing their sociodemographic and behavioral characteristics and lifestyle changes during the pandemic. A total of 1000 questionnaires were completed. Most participants (63.5% women, mean age 40 ± 13.1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
(48 reference statements)
1
20
0
Order By: Relevance
“…In addition, there is evidence suggesting that HCWs’ lifestyle changes can shape their behaviour, and HCWs’ attitudes towards vaccination may be associated with changes in lifestyle. This was reported in a recent study in Italy where Gallé and colleagues assessed changes in public HCWs’ lifestyle during the COVID-19 pandemic era [ 38 ]. In a total of 1000 public HCWs that completed the study questionnaire, observed changes included that more than half of the HCWs had normal weight, were non-smokers, and slept at least 6 h per night.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, there is evidence suggesting that HCWs’ lifestyle changes can shape their behaviour, and HCWs’ attitudes towards vaccination may be associated with changes in lifestyle. This was reported in a recent study in Italy where Gallé and colleagues assessed changes in public HCWs’ lifestyle during the COVID-19 pandemic era [ 38 ]. In a total of 1000 public HCWs that completed the study questionnaire, observed changes included that more than half of the HCWs had normal weight, were non-smokers, and slept at least 6 h per night.…”
Section: Introductionmentioning
confidence: 78%
“…HCWs’ attitudes towards vaccination may be associated with changes in lifestyle (such as weight, diet, physical activity, and sleep), as shown in a recent study in Italy by Gallé and colleagues assessing changes in public HCWs’ lifestyle during the COVID-19 pandemic [ 38 ]. However, we did not test for the impact of HCWs’ lifestyle changes with respect to influenza vaccines at the start of the COVID-19 vaccine rollout in Cape Town.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature suggested that public health workers are experiencing workload changes because of their role in preventing and controlling the spread of COVID-19. They are also experiencing lifestyle changes during the COVID-19 pandemic such as physical inactivity and daily sweet food consumption [ 16 ]. Healthcare professionals are more likely to have access to the vaccine at an early stage and play a significant role in providing information about the vaccine for the general population.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we could only analyze the support measures that were implemented in our hospitals. Other support measures have also been described as useful in the literature, such as working on an effective and clear communication between HCWs, the adaptation of the workplace structure (with, for example, the implementation of regular breaks and of relaxation areas, the adaptation of time tables), training courses for HCWs to better deal with difficult situations and the promotion of good health behaviors such as providing access to physical activity facilities [ 14 , 15 , 19 , 25 ].…”
Section: Discussionmentioning
confidence: 99%